Insights into the Future Computers – The Bio computers - Nirupa Koshti; Apeksha Kadam; Rajashree Mashru (International Journal of Pharma and Bio Sciences, 2020)
The computation can be performed by natural and man-made devices. Man-made computers are made from silicon chips, whereas natural computers, such as the brain, uses cells and molecules. Conventional computers are good but they still require some advancements for handling complex hard problems. Silicon chips used in conventional computers are made of toxic substances such as arsenic which can cause damage to nerve cells and immune system, especially in children. Silicon chips consume lots of energy and dissipate heat. To deal with issues resulting from the limitations of conventional computers, biocomputer is emerging as a promising alternative. Biocomputers are result of amalgamation of two fields - computer science and biology. Interest in such biomolecular computing devices is strong, mainly because of their ability (unlike electronic computers) to interact directly with biological systems and even living organisms. No interface is required since all components of molecular computers, including hardware, software, input and output, are molecules that interact in solution along a cascade of programmable chemical events. Biological organisms regularly convert data about the macroscopic world gathered by senses in to a form that influences biology at molecular level. A new computing paradigm enables the researcher to build an array or a system of biosensors that has the ability to detect or target specific types of cells that could be found in the patient's body. A biocomputer has the potentials of parallel and distributed processing, massive storage of data, scalability, adaptability (through learning or evolution) and flexibility to minimize costs. Rational design and engineering biocomputers can greatly enhance our ability to study and control biological systems. This review is written with a perspective of delivering a bird’s eye view about biocomputers through coalescence of crucial elements collected from different developments that took place at different time intervals rather than limiting the view only to one development. We also tried to throw light on various types and mechanism of working of biocomputers, along with the insights on current and future perspectives, thus sufficing the curiosity of researchers that want to pursue their research in the field of biocomputers.